2022
DOI: 10.47162/rjme.63.2.05
|View full text |Cite
|
Sign up to set email alerts
|

Telocytes inside of the peripheral nervous system – a 3D endoneurial network and putative role in cell communication

Abstract: In this paper, we developed the hypothesis concerning the reasons to assimilate endoneurial fibroblast-like dendritic phenotype [shortly termed endoneurial dendritic cells (EDCs)] to the endoneurial telocytes (TCs). We reviewed the literature concerning EDCs status and report our observations on ultrastructure and some immune electron microscopic aspects of the cutaneous peripheral nerves. Our data demonstrate that EDCs long time considered as fibroblasts or fibroblast-like, with an ovoidal nucleus and one or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 109 publications
0
13
0
Order By: Relevance
“…49 Telopode (Tps) was considered crucial for the cell junction formation between TCs and other types of cells. 50 Tps was significant in TCs dominated cell-cell communication. 51 Research showed that TCs co-cultured with peritoneal macrophages could inhibit apoptosis through paracrine effects.…”
Section: F I G U R Ementioning
confidence: 87%
“…49 Telopode (Tps) was considered crucial for the cell junction formation between TCs and other types of cells. 50 Tps was significant in TCs dominated cell-cell communication. 51 Research showed that TCs co-cultured with peritoneal macrophages could inhibit apoptosis through paracrine effects.…”
Section: F I G U R Ementioning
confidence: 87%
“…Telocytes (interstitial or stromal cells), are present throughout the body, can communicate through long “tentacles” that reach between tens and hundreds of micrometers, called telopods [ 32 ]. Telopods touch not only other telocytes but cells of different nature, close and distant [ 33 ]. Nanotunnels allow to transport different biochemicals and extracellular vesicles for the regulation of cellular morphogenesis, regeneration and metabolism, and influence the function toward a physiological or pathological environment [ 34 ].…”
Section: Reviewmentioning
confidence: 99%
“…Moreover, TCs have also been observed in tumour tissues such as breast tumour and basal cell carcinoma, possibly playing roles in promoting invasive behaviour of microtumours. 65,66…”
Section: Tissue Distribution Of Telocytesmentioning
confidence: 99%
“…Particularly, TCs have also been documented to be involved in regenerative processes due to their tandem with SCs in a variety of organs, such as aorta, 53 eye, 54 heart, 3,55,56 liver, 57,58 lungs, 38,39,59 skeletal muscles, 60–62 skin, 47 meninges and choroid plexus, 41,63,64 which are tissues contiguous to the brain where neural SC niches are located except for typical locations (e.g., subventricular zone and/or subgranular zone). Moreover, TCs have also been observed in tumour tissues such as breast tumour and basal cell carcinoma, possibly playing roles in promoting invasive behaviour of microtumours 65,66 …”
Section: Tissue Distribution Of Telocytesmentioning
confidence: 99%